A construção da confiança na decisão da compra online - Devens, Gabriela Rossi (2017)
Purpose – This study aims to understand which attributes influence the creation of trust that leads to an online purchase. These attributes will be categorized between the features of the e-commerce and the costumers’ characteristics and believes that affect the trust on online shopping. In addition, attributes found in previous studies, focused on more mature markets, were considered in order to understand the current Brazilian market. Methodology – The present research is exploratory and qualitative. Focus groups and interviews were conducted among customers with strong online shopping habits and others with certain level of resistance. Results – This study demonstrates that the costumer’s characteristics prevails over the e-commerce features on the creation of trust for the purchase decision. Among them, the most relevant attributes found in both studied groups were brand awareness and recommendations from acquaintances. Limitations – Further research is needed with a higher number of interviews that diversify the costumer’s profiles. Furthermore, shopping awareness and the influence of social media should be taken into account. Practical implications – These results identify features for the creation of trust and contribute for the implementation of new strategies for the increase of online shopping. Originality – This study contributes for the understanding of underlaying consumer’s characteristics and categorized brand awareness, influence in decision making, knowledge of rules and search for information.